Cadaveric bone marrow mesenchymal stem cells: first experience treating a patient with large severe burns - Mansilla, Eduardo (2015)
Background: In January 2005, Rasulov et al. originally published ?First experience in the use of bone marrowmesenchymal stem cells (MSCs) for the treatment of a patient with deep skin burns. Here, we present the firstever treated patient with cadaveric bone marrow mesenchymal stem cells (CMSCs) in the history of Medicine.Methods: A young man, who severely burned 60 % of his total body surface with 30 % of full-thickness burns whileworking with a grass trimmer that exploded, was involved in the study. MSCs were obtained from the bone marrow ofa cadaver donor in a routine procurement procedure of CUCAIBA, the Province of Buenos Aires, Argentina, Ministry ofHealth, Transplantation Agency, cultured, expanded, and applied on the burned surfaces using a fibrin spray after earlyescharotomy.Results: So far, our preliminary experience and our early results have been very impressive showing an outstandingsafety data as well as some impressive good results in the use of CMSCs.Conclusions: Based on all this, we think that improvements in the use of stem cells for burns might be possible in thenear future and a lot of time as well as many lives could be saved by many other research teams all over the world.CMSCs will probably be a real scientific opportunity in Regenerative Medicine as well as in Transplantation.